Detailed Review on Gestational Diabetes Mellitus with Emphasis on Pathophysiology, Epidemiology, Related Risk Factors, and its Subsequent Conversion to Type 2 Diabetes Mellitus - Gajera, Dhruvil; Trivedi, Vishva; Thaker, Priyanshu; Rathod, Mrudang; Dharamsi, Abhay (Hormone and Metabolic Research, 2023)
Any degree of glucose intolerance during the pregnancy of a women is termed as Gestational Diabetes Mellitus (GDM). It may further develop into Type 2 Diabetes Mellitus (T2DM) later in life. GDM affects both mother and infant in multiple ways and there are various factors that predispose the development of GDM.The primary objective of this review is to describe the various aspects related to GDM and the subsequent risk of developing T2DM later in life.We reviewed freely accessible, full-text articles, available in PubMed, Google Scholar, and MEDLINE in the English language, till August 2022 pertaining to GDM.The pathophysiology of underlying glucose intolerance has been discussed, including the various factors like β-Cell dysfunction, chronic insulin resistance, adiponectin, insulin resistance. GDM affects pregnancies world-wide, but it is higher in the South-east Asia, northern America and Caribbean, south and central America regions. Along with ethnicity, various modifiable and non-modifiable risk factors also play a major role in development of disease. Although no standard diagnostic criteria is accepted world-wide for screening of GDM, but the one-step and two-step approach has made quite a difference. The risk of developing T2DM after GDM is well documented, and it increases with age. GDM leads to an onset of diabetes in the family at a young age, it leads to poor consequences on the health of both the mother and infant. Standard diagnostic criteria, proper education and counselling of the mother is required to tackle the condition.
Keywords: gestational diabetes mellitus; diabetes mellitus type 2; Impaired glucose tolerance; metabolic syndrome